2015
DOI: 10.1016/j.biopsych.2014.12.009
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA and Posttranscriptional Dysregulation in Psychiatry

Abstract: Psychiatric syndromes, including schizophrenia, mood disorders, and autism spectrum disorders, are characterized by a complex range of symptoms, including psychosis, depression, mania, and cognitive deficits. Although the mechanisms driving pathophysiology are complex and remain largely unknown, advances in the understanding of gene association and gene networks are providing significant clues to their etiology. In recent years, small noncoding RNA molecules known as microRNA (miRNA) have emerged as potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
126
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(132 citation statements)
references
References 85 publications
4
126
0
2
Order By: Relevance
“…It has been shown that many diseases including a variety of cancers, 1−3 psychiatric syndromes, 4 diabetes, 5 and cardiovascular diseases 6,7 correlate to dysregulation of these small RNAs. With a high value, miRNAs have gained increasing popularity as potential novel biomarkers in disease diagnosis and prognosis.…”
mentioning
confidence: 99%
“…It has been shown that many diseases including a variety of cancers, 1−3 psychiatric syndromes, 4 diabetes, 5 and cardiovascular diseases 6,7 correlate to dysregulation of these small RNAs. With a high value, miRNAs have gained increasing popularity as potential novel biomarkers in disease diagnosis and prognosis.…”
mentioning
confidence: 99%
“…One level of posttranscriptional gene regulatory mechanism associated with BD involves microRNAs (miRNAs). 101 miRNAs are small noncoding RNA molecules that play an important role in regulating gene expression via complementary binding to the 3′-untranslated region of a specific mRNA molecule. 102 Genetic variations in miRNA binding sites could alter gene expression, which could modulate neuronal development and plasticity.…”
Section: Posttranscriptional Dysregulation and Micrornas In Bdmentioning
confidence: 99%
“…A recent review that assessed a wide variety of differentially regulated miRNA reported, on postmortem examination, an upregulation of seven miRNAs and a downregulation of eight miRNAs in the dorsolateral prefrontal cortex of patients with BD in comparison to controls (Table 1). 101,105 Another study also validated gene expression using quantitative realtime polymerase chain reaction (qRT-PCR) and reported that patients with BD presented a trend toward decreased miRNA expression levels, specifically in 19% of miRNAs that were analyzed in the prefrontal cortex (Table 1). 106 More recently, a negative correlation was found between miRNA expression and their gene targets, 105 suggesting that miRNA may act to negatively regulate gene expression.…”
Section: Posttranscriptional Dysregulation and Micrornas In Bdmentioning
confidence: 99%
“…Histone modification and DNA methylation in response to experience, inflammation, the illness, and the medications used to treat it can induce or suppress multiple genes, and genotype itself can affect methylation of regulatory sites that leads to epigenetic changes in brain development [51]. Micro-RNAs and short interfering RNAs are short, noncoding posttranslational regulators of gene expression that target hundreds of mRNA transcripts to influence gene networks [27,52,53]. The expression of genes for CYP450 enzymes is altered by promoter methylation, micro-RNAs associated with inflammation and other illnesses [27], and some medications [54], resulting in an altered CYP450 phenotype.…”
Section: Gene Expressionmentioning
confidence: 99%